2004
DOI: 10.1139/x04-047
|View full text |Cite
|
Sign up to set email alerts
|

A biogeochemical analysis of the Pocono till barrens and adjacent hardwood forest underlain by Wisconsinan and Illinoian till in northeastern Pennsylvania

Abstract: We assessed soil and vegetation nutrient capital in the landscape mosaic of till barrens and hardwood forests on the Pocono Plateau in northeastern Pennsylvania. These shrublands, which contain an unusual abundance of rare species, occur primarily on Illinoian-aged glacial till, though some patches grow on Wisconsinan till. We hypothesized that barrens soil and vegetation contain smaller quantities of nutrients than forest soil and vegetation, and under the same vegetation, Illinoian till soils have a smaller … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 18 publications
1
2
0
Order By: Relevance
“…Across all species, foliar N concentrations were consistently highest in seedlings grown in native till soils, and foliar N had a significant positive effect on PI ABS on all tree species except serviceberry. The black birch, red oak, and silver maple seedling foliar N concentrations were lower than published values or thresholds for deficiency (Pardo et al 2004; Castro et al 2007; Showalter et al 2010), while serviceberry foliar N was comparable to published values found in saplings at New York City restoration sites and elsewhere (Pardo et al 2004; Wibiralske et al 2004; Falxa‐Raymond et al 2014). However, foliar N did not have a positive effect on seedling biomass of any species and had a significant negative effect on red oak and serviceberry biomass (primarily driven by declines in foliar biomass).…”
Section: Discussionsupporting
confidence: 51%
“…Across all species, foliar N concentrations were consistently highest in seedlings grown in native till soils, and foliar N had a significant positive effect on PI ABS on all tree species except serviceberry. The black birch, red oak, and silver maple seedling foliar N concentrations were lower than published values or thresholds for deficiency (Pardo et al 2004; Castro et al 2007; Showalter et al 2010), while serviceberry foliar N was comparable to published values found in saplings at New York City restoration sites and elsewhere (Pardo et al 2004; Wibiralske et al 2004; Falxa‐Raymond et al 2014). However, foliar N did not have a positive effect on seedling biomass of any species and had a significant negative effect on red oak and serviceberry biomass (primarily driven by declines in foliar biomass).…”
Section: Discussionsupporting
confidence: 51%
“…These values are lower than other reported masses for the Catskills and the Pocono region of Pennsylvania. The average O‐horizon mass ranged from 12 to 20 kg/m 2 at four sites sampled in the early 1990s in the Pocono Barrens . A study conducted in the Catskills in 2000–2003 reported average O‐horizon masses of 6–10 kg/m 2 .…”
Section: Discussionmentioning
confidence: 99%
“…Many studies (e.g. Kulmatiski et al, 2003;Wibiralske et al, 2004) used pits only 50 cm square (0.25 m 2 ), which expedites the process, but limits the total depth that can be excavated cleanly; our 0.5 m 2 pits allow a person to work from inside the pit. Richter et al (1989) excavated small pits, only 0.05 m 2 , to a depth of 40 cm.…”
Section: Reviewing the Quantitative Pit Methodsmentioning
confidence: 99%